Whole-Brain Reconstruction of Neurons in the Ventral Pallidum Reveals Diverse Projection Patterns - Feng, Qiru; An, Sile; Wang, Ruiyu; Lin, Rui; Li, Anan; Gong, Hui; Luo, Minmin (Frontiers in Neuroanatomy, 2021)
The ventral pallidum (VP) integrates reward signals to regulate cognitive, emotional, and motor processes associated with motivational salience. Previous studies have revealed that the VP projects axons to many cortical and subcortical structures. However, descriptions of the neuronal morphologies and projection patterns of VP neurons at the single-neuron level are lacking, hindering understanding of the wiring diagram of the VP. Here, we used recently developed progress in robust sparse labeling and fluorescence micro-optical sectioning tomography imaging system (fMOST) to label mediodorsal thalamus-projecting neurons in the VP and obtain high-resolution whole-brain imaging data. Based on these data, we reconstructed VP neurons and classified them into three types according to their fiber projection patterns. We systematically compared the axonal density in various downstream centers, and analyzed the soma distribution and dendritic morphologies of the various subtypes at the single neuron level. Our study thus provides a detailed characterization of the morphological features of VP neurons, laying a foundation for exploring the neural circuit organization underlying the VP’s important behavioral functions.